ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA OPERASI PECAHAN MENGGUNAKAN PROSEDUR NEWMAN BERDASARKAN GENDER KELAS V SD MUHAMMADIYAH PERUMNAS KOTA MAKASSAR - Muarif, Andi Asratul; Ernawati; Wahyudi, Andi Ardhila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Andi Asratul Muarif 2026. Analysis of Students' Errors in Solving Fraction Operation Story Problems Using Newman Procedure Based on Gender of Fifth Grade of Muhammadiyah Perumnas Elementary School, Makassar City. Thesis. Department of Elementary School Teacher Education, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar Supervisor I Ernawati and Supervisor II Andi Ardhila Wahyudi. This study aims to analyze the errors of fifth grade students of Muhammadiyah Perumnas Elementary School, Makassar City in solving fraction operation story problems using Newman procedures based on gender. This type of research uses a qualitative descriptive approach, the sample in this study is a subject of 20 students, then the researcher selected 6 students consisting of 3 male students and 3 female students with ability categories (high, medium, and low). The sampling technique uses propositional sampling. Data collection techniques are in the form of tests, interviews and documentation and data analysis techniques are in the form of analyzing student answer sheets and interview analysis and validity tests using technical and time triangulation. Based on the research results, the Newman procedure is effective for identifying student errors in solving fraction story problems, where the types of errors vary based on the level of ability in high-ability students, males (masculine) make errors in writing the final answer and female students (feminine) make errors in transformation, process skills and final writing. Medium-ability students in male students (masculine) have errors in transformation, process skills and writing the final answer are more constrained at the transformation and calculation process stages, in female students (feminine) tend to make errors in final writing, transformation, process skills while low-ability students in male students (masculine) make errors in transformation, process skills and writing the final answer while female students (feminine) have experienced difficulties from the stage of understanding the problem to writing the final answer. Meanwhile, if viewed from the gender aspect, both males and females make errors in almost all stages of the Newman procedure except reading errors and the tendency of different types of errors.